Global agricultural extension staff functional competencies - Davis, Kristin E.; Joseph, Jeanelle; Barry, Tessa; von Maltitz, Lindie; Van Niekerk, Johan; Ngomane, Tsakani; Rasoanindrainy, Andrianjafy (International Food Policy Research Institute, 2021)
Public and nonpublic extension and advisory services are both key to sustainable agriculture, resilient livelihoods, and inclusive growth1. The Global Forum for Rural Advisory Services (GFRAS) has called for “the new extensionist”(Davis and Sulaiman 2014), emphasizing the functional competencies needed to help clientele cope with complex challenges such as climate change and nutrition. Since 2015 the GFRAS “New Extensionist Learning Kit” (NELK)has been equipping extension agents globally with functional competencies through face-to-face, online, and blended learning(AFAAS 2018). Competencies are defined in many different ways (Westera 2021). For this paper, we define competency simply as “the capability to perform actions which add value” (Mulder, 2012: 319). Functional competencies(the so-called soft skills, as distinct from more technical areas in agriculture, animal sciences, natural resources, etc.)have not been well documented in the academic literature, especially with respect to digitally enabled extension (Strong et al. 2014). According to Khalil and colleagues (2009), competencies such as leadership, communication, program planning, and evaluation are important factors for performance of extension staff. Digital skills are also becoming more important for extension officers. The utilization of digital technology (online modules, webinars) to deliver the NELK modules provides the opportunity to use expertise available globally to train many extension professionals at the same time. How ready, however, are extension officers globally to use such digital approaches –for continuous professional development and learning and also for outreach? Spielman and colleagues (forthcoming) developed an index of “digital readiness” of extension agents in Rwanda. Digital readiness is also referred to as Networked Readiness Index or Technology Index, and indicates the status and growth of information and communications technologies (ICT) and how ICTs are effectively used to achieve maximum benefits to the country and its citizens (Bharatula and Murthy 2020).